Extended Anterolateral Infralabyrinthine Transjugular Approach for Microsurgical Resection of Giant Glomus Vagale Tumor: Operative Video and Technical Nuances - Liu, James K. (J Neurol Surg B Skull Base, 2021)
Glomus vagale tumor is a paraganglioma of the vagus nerve. It is a rare type of benign tumor that occupies the head and neck and skull base regions. Patients often present with lower cranial nerve dysfunctions such as difficulty swallowing, tongue weakness, and hoarseness. Surgical treatment can be complex and difficult due to its high vascularity, frequent involvement of lower cranial nerves, and surrounding critical vascular structures. In this operative video, we demonstrate an extended anterolateral infralabyrinthine transjugular approach for microsurgical resection of a giant glomus vagale tumor in a 53-year-old male who presented with an enlarging neck mass, difficulty swallowing, right tongue weakness, and hoarseness. Imaging revealed a giant glomus vagale tumor in the right parapharyngeal space extending into the jugular foramen with occlusion of the internal jugular vein. After preoperative embolization, the patient underwent a near-total resection of the tumor with a small microscopic residual at the pars nervosa. In summary, the extended anterolateral infralabyrinthine transjugular approach is a useful strategy for removal of giant glomus vagale tumors extending into the skull base. The surgical technique and nuances are described in a step-by-step fashion in this illustrative operative video. The link to the video can be found at: https://youtu.be/L0EosQK95LE .